Possibility of glyphosate-resistant goosegrass (Eleusine indica) in citrus fields in Rejang Lebong Districts, Bengkulu, Indonesia - MARULAK SIMARMATA; REKO APRIANTONEDI; NANIK SETYOWATI; HESTI PUJIWATI (Society for Indonesian Biodiversity, 2023)
Abstract. Simarmata M, Apriantonedi R, Setyowati N, Pujiwati H. 2023. Possibility of glyphosate-resistant goosegrass (Eleusine indica) in citrus fields in Rejang Lebong Districts, Bengkulu, Indonesia. Biodiversitas 24: 3633-3638.Weed abundances dominated by goosegrass (Eleusine indica L.) are a major constraint in the citrus fields of Rejang Lebong District, Province of Bengkulu, Indonesia. The objectives of this research were to investigate weed control methods applied by citrus farmers, analyze the dominant weed, and study the possibility of glyphosate resistance in goosegrass. A survey was conducted by interviewing three citrus farmers regarding weed control measures, followed by weed assessment in 10 sampling plots of each location. Then, field trials were conducted to evaluate glyphosate efficacy on weeds in the three locations of citrus fields. The survey found that glyphosate has been applied for weed control up to 4 L ha-1( 1.92 kg a.i. ha-1 of isopropyl amine salt) 2 to 3 times a year, and the farmers found that some weeds were resistant to glyphosate. Weed assessment showed that goosegrass is a dominant species with a summed dominance ratio (SDR) of 67.1, 70.8, and 79.0% at each location, respectively. The field trials observed that the levels of survival weeds in the experimental plots treated with glyphosate at 0.5, 1.0, 2.0, 4.0, and 8.0 L ha-1were 94-95%, 83-85.3%, 70-73.3%, 20-29%, and 10-12.3%, respectively. Goosegrass was identified as the survivor's weeds. The glyphosate doses (LD50) required to eradicate 50% of the weed populations ranged between 2 and 4 L ha-1 at the three sites. This study proved that goosegrass in the citrus groves of Rejang Lebong District, Bengkulu, is resistant to glyphosate.